Prediction of genetic gains through selection of sweet potato accessions - Vargas,Pablo F (2020)
ABSTRACT Due to the high genetic variability found in sweet potato and a low number of cultivars available on the market, there are opportunities for necessary improvements in crop breeding programs. The selection indexes are a favorable strategy to achieve higher yields through genetic gains obtained with the future population. Thus, the objective was to evaluate the selection gain of agronomic characters from sweet potato accessions for root production and dual-aptitude. 95 accessions and two commercial cultivars (Braslandia Branca and Brazlândia Roxa) were evaluated. A randomized block design with three replications of ten plants per plot was used. The index proposed by Mulamba & Mock was used to select superior individuals. The evaluated population showed high genetic variability providing considerable selection gains, being recommended some clones for tests of value for cultivation and use. The VR13-61 accession was the most recommended for root production and VR13-11 and VR13-22 for dual-aptitude.